Retrospective mortality cohort study of Italian workers compensated for silicosis. Issue 11 (17th July 2006) - Marinaccio, A; Scarselli, A; Gorini, G; Chellini, E; Mastrantonio, M; Uccelli, R; Altavista, P; Pirastu, R; Merlo, D F; Nesti, M
Abstract : Objectives: To estimate cause specific mortality in a large cohort of Italian workers compensated for silicosis. Methods: The cohort included 14 929 subjects (14 098 men and 831 women) compensated for silicosis between 1946 and 1979, alive on 1 January 1980, and resident in Tuscany (a region of central Italy with 3 547 000 inhabitants). Mortality follow up ranged from 1980 to 1999. Vital status and the causes of death were determined by linkage with the regional mortality registry and with the national mortality database. The cohort mortality rates were compared to the rates of the local reference population. SMRs and their 95% confidence intervals were computed assuming a Poisson distribution of the observed deaths. Specific SMR analyses were performed according to the level of disability, the year of compensation assignment, and the job type. Results: A significant excess mortality was observed in male silicotics for cancer of the lung, trachea, and bronchus and cancer of the liver, respiratory diseases (silicosis, asbestosis, antracosilicosis, and other pneumoconiosis), and for tubercolosis. Statistically significant mortality excess was observed in female silicotics for respiratory diseases (specifically silicosis and other pneumoconiosis) and tuberculosis. Analyses for period of compensation assignment showed a twofold increased SMR for biliary tract cancer among female workers and for liver cancer among male workers compensated before 1970. Conclusions: The excess mortality from respiratory tract cancers and respiratory tract diseases detected in Italian compensated silicotics are in agreement with previous epidemiological studies. Although the twofold increased risk for liver cancer among males is suggestive of a possible association with silica dust exposure, the finding needs to be confirmed.